1994
DOI: 10.1007/bf02093780
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide increases thresholds of colonic visceral perception in IBS patients without modifying muscle tone

Abstract: Effects of octreotide (1.25 micrograms/kg subcutaneously) on colonic tone and visceral perception were evaluated in 10 IBS patients, using a barostat and compared to placebo in a double-blind crossover study. Colonic sensory thresholds were also studied in healthy controls for comparison with IBS patients. Colonic tone was reflected by variations in volume of the barostat balloon. Baseline volume was 117 +/- 38 ml and was not modified by placebo (122 +/- 40 ml) or octreotide (106 +/- 42 ml). After the meal, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 29 publications
4
55
0
1
Order By: Relevance
“…98 A schematic of receptor targets for SST receptor agonists is shown in Figure 2. In humans, octreotide, a non-selective SST2, SST3 and SST5 receptor agonist, has been demonstrated to have potent viscero analgesic, [99][100][101] as well as GI motility, effect. 102 Several pharmacodynamic studies have…”
Section: Somatostatin Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…98 A schematic of receptor targets for SST receptor agonists is shown in Figure 2. In humans, octreotide, a non-selective SST2, SST3 and SST5 receptor agonist, has been demonstrated to have potent viscero analgesic, [99][100][101] as well as GI motility, effect. 102 Several pharmacodynamic studies have…”
Section: Somatostatin Receptor Agonistsmentioning
confidence: 99%
“…[99][100][101][103][104][105][106] Preliminary evidence from an 8-week controlled clinical treatment trial 107 showed that octreotide treatment was associated with a reduction in the perception of barostat-induced rectal distension in non-constipated IBS patients. In addition, octreotide treatment was found to reduce the abdominal complaints and improve the stool consistency, suggesting an overall beneficial effect.…”
Section: Somatostatin Receptor Agonistsmentioning
confidence: 99%
“…Preliminary data have sug gested efficacy in the treatment of functional dyspepsia [103,104], and it has been shown to block the effects of intraduodenal fat on de laying gastric emptying [105]. Octreotide, a somatostatin analogue, has increased colonic thresholds to discomfort and pain without modifying tone [106]. Fedotozine, a peripher al kappa opioid receptor agonist, has been shown to modulate the cologastric reflex pro duced by intraluminal balloon distension in dogs [107], In the human colon, it also ap pears to increase pain thresholds [108].…”
Section: Drug Therapymentioning
confidence: 99%
“…A octreotida, análogo sintético do hormônio natural somatostatina, em injeção subcutânea, aumenta significativamente o limiar para a percepção da distensão do intestino grosso em pacientes com a síndrome do intestino irritável (6) , sendo, porém, incerto se afeta a sensibilidade gastroduodenal em pacientes com a dispepsia funcional.…”
Section: Drogas Que Reduzem Ou Modificam a Sensibilidade Visceralunclassified